2019
DOI: 10.1103/physreve.99.063107
|View full text |Cite
|
Sign up to set email alerts
|

Understanding droplet collisions through a model flow: Insights from a Burgers vortex

Abstract: We investigate the role of intense vortical structures, similar to those in a turbulent flow, in enhancing collisions (and coalescences) which lead to the formation of large aggregates in particle-laden flows. By using a Burgers vortex model, we show, in particular, that vortex stretching significantly enhances sharp inhomogeneities in spatial particle densities, related to the rapid ejection of particles from intense vortices. Furthermore our work shows how such spatial clustering leads to an enhancement of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Other key ingredients in the problem of cough/sneeze flows are the inertia of the droplets, and the effect of phase change on the droplets and on the turbulence. We have studied the dynamics of droplets in turbulent flow (e.g., Govindarajan 2015, 2017;Deepu et al 2017;Agasthya et al 2019;Picardo et al 2019;, and the ejection from a cough is precisely such a flow. Droplet inertia and gravity bring new physics to this problem, and we plan to handle these effects in two ways:…”
Section: Dynamics Of Small Water Dropletsmentioning
confidence: 99%
“…Other key ingredients in the problem of cough/sneeze flows are the inertia of the droplets, and the effect of phase change on the droplets and on the turbulence. We have studied the dynamics of droplets in turbulent flow (e.g., Govindarajan 2015, 2017;Deepu et al 2017;Agasthya et al 2019;Picardo et al 2019;, and the ejection from a cough is precisely such a flow. Droplet inertia and gravity bring new physics to this problem, and we plan to handle these effects in two ways:…”
Section: Dynamics Of Small Water Dropletsmentioning
confidence: 99%
“…However, one can gain a basic understanding of how such structures may influence the motion and collisions of droplets by using model vortex flows. Such an analysis was carried out in two-dimensions, using point and gaussian vortices, by Ravichandran et al [78] and Deepu et al [30], and later extended to a threedimensional Burgers vortex [21] by Agasthya et al [2]. These studies show that particles near the core of a strong vortex are ejected more rapidly than particles farther away.…”
Section: Microphysics Without Thermodynamicsmentioning
confidence: 99%
“…This leads to a large increase in the local particle density around the periphery of the vortex (Fig. 3 of [2]), as well as large relative velocities between neighbouring particles (caustics). These factor combine to significantly enhance collisions in the vicinity of the vortex.…”
Section: Microphysics Without Thermodynamicsmentioning
confidence: 99%
“…It is reported that the straining zones contribute predominantly to head-on collisions, while intense vortices could rapidly eject particles and cause violent collisions (Perrin & Jonker 2014, 2016; Agasthya et al. 2019; Picardo et al. 2019; Chen & Li 2020).…”
Section: Introductionmentioning
confidence: 99%